ISLAMIC FINTECH COLLABORATION: INDONESIA'S ECONOMIC READINESS TOWARDS A NEW NORMAL ERA - Elida Barus; Andri Soemitra (Proceeding International Seminar of Islamic Studies, 2021)
The impact of the COVID-19 pandemic has an effect on the weak economy, so that the existence of Islamic microfinance institutions, especially Islamic cooperatives, has decreased with many obstacles.Therefore, various capital innovations are needed with Company to Company (C2C) collaboration.This collaboration needs to be supported by an accommodating system, so that its development can provide benefits to users, one of which is influenced by the use of financial technology in this case is Ammana.id, this is Islamicfintechwhich is also assisted by other actors such as regulators,conceptors, owners,entors.andsociety asparticipationby analyzing qualitatively, namely the development strategy of sharia cooperatives withfintechcollaboration with the interpretive structure modeling(ISM).This paper finds that the elements of actors, namely the Office of Cooperatives and Small and Medium Enterprises, are key elements so that it needs to be focused on developing sharia regulations which are then assisted by academics as a drafter in the development of Islamic microfinance institutions ..Keyword: collaboration, Sharia Financial Technology, economics, New Normal Era